Effects of external and internal attention focus training on foot-strike patterns in running - Chow, J. Y.; Woo, M. T.; Koh, M. (International Journal of Sports Science and Coaching, 2014)
The provision of instructions is an important task constraint when altering movement behaviours. Using instructions as a form of task constraint could be an effective approach to help learners improve their performances. Specifically, changing running gait from a heel to forefoot strike pattern can reduce incidences of injuries. By providing different attentional instructions, external and internal focus instructions, which emphasise movement effect and movement form respectively, can be used to alter foot strike patterns in running gait. The purpose of this study was to investigate the effectiveness of external or internal focus instructions in facilitating a change from a heel strike to a forefoot strike pattern. Sixteen participants (9 males, 7 females), were randomly assigned to either an external focus condition (n=8) or an internal focus condition (n=8). Participants underwent six training sessions with their respective instructional conditions over three weeks with 10 one-minute running trials per session during the intervention phase. A 3D motion analysis system was used to determine kinematic changes between pre and post-test sessions. Both external (0.025m ± 0.006) and internal (0.027m ± 0.008) participants showed a significant change in calcaneus displacement at initial contact (IC) by post-test, which indicates the change from heel strike to forefoot strike pattern. However, cycle time and stride length were not significantly different at post-test for participants in internal and external conditions. The effectiveness of both focus instructions could be task and individual dependent.